Online identity presentation across genders and its influence on online friendship and relationship in Saudi Arabia - Ades, Andaleeb Sadi R (2019)
Since the introduction of new technology like social media, new norms have emerged in the society too. Online relationship and online friendship across genders have become a new trend even to the conservative societies like Saudi Arabia. Normally, these kinds of friendships and relationships are strongly rejected offline. This study examined the level of online social interaction across gender in Saudi, the influence of online identity presentation on online social interaction, and gender as a moderating variable between online identity presentation and online social interaction. A total of 450 Saudi Facebook users aged between 18 to above 50 years old, from three cities: Mecca, Jeddah and Riyadh, has participated in this research, by answering a self-administered questionnaire survey. SEM was used to test the twenty-four hypothesis of this study. Results of the study show that, both online friendship and online relationship existed in Saudi. This indicates that there is a significant positive relationship between online identity presentation and online friendship. However, the study also found that there are only three factors have significant positive relationship between online identity presentation and online relationship. The findings of the study revealed that gender moderates the relationship between five paths only (attitude and friendship, perceived behaviour and friendship, visual and friendship, textual and friendship, and duration and friendship). The study concludes that the online social interaction across gender in Saudi, reached the affective and stable stages of the interactions among the Facebook users. Further, the study also provided a theoretical contribution to the development of a more differentiated model in measuring the online social interaction intimacy by merging three theories and one moderating variable. The new model explained 15.4% of online friendship and 68% of online relationship of the dependent variables. The findings of the study are useful to the web designers in the development of social interaction sites, where they could consider the incorporation of visual elements that suit a society like Saudi. The findings are also beneficial to the policymakers and researchers by giving them a clear vision about how Saudi Arabians present and behave themselves online.